Membangun Pendidikan Inklusif-Pluralis: Pengalaman Islam - Zuly Qodir (Jurnal Orientasi Baru, 2008)
There are different theoretical paradigms within the world of education. Each has its own ideology. In its turn, an ideology determines goal of education and its way of proceedings, curriculum and its educational methodology, quality of the graduates and its alumni. Within a context of sosial and cultural pluratity of the Indonesian society, an inclusive and pluralistic paradigm is recommended. Indeed, such paradigm is in line with the teaching of Islam.